LEACH Algorithm Based on Load Balancing - Wangang Wang; Yong Peng (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper discusses advantages of LEACH Algorithm and the existing improved model which takes the famous hierarchy clustering routing protocol LEACH Algorithm as researching object. Then the paper indicates the problem that in the algorithm capacity factor of cluster head node is not taken into account leading the structure of clusters to be not so reasonable. This research discusses an energy-uniform cluster and cluster head selecting mechanism in which “Pseudo cluster head” concept is introduced in order to coordinate with “Load Monitor” Mechanism and “Load Leisure” Mechanism to maintain load balancing of cluster head character and stability of network topology. On the basis of LEACH Protocol improving algorithm of LEACH-C, CEFL and DCHS. NS2 simulation instrument is applied to do simulation analysis on the improved algorithm. Simulation result shows that LEACH-P Protocol effectively increase energy utilization efficiency, lengthens network lifetime and balances network load. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3287